Tourism and sustainable economic development - Salvo Creaco; Giulio Querini (European Regional Science Association (ERSA), 2001)
The interest in sustainable tourism reflects the growing recognition that the industry, tourists and natural resources are inter-linked and that these elements depend each other for successful long term sustainability at appropriate decision-making levels. While much research has been done on how to progress towards more sustainable kind of tourism, much needs to be undertaken to foster the practical application of the concept. This paper is part of this ongoing effort. Having expressed the exigency to build the debate on sustainable tourism on sound economic foundations, and having outlined the capacity of economists to provide such theoretical foundations by stretching the orthodox economic theory to incorporate sustainable issues, the paper shows the evolution of European policy for sustainable tourism together with an analysis of strategies and instruments which appear to be necessary if we are to reconcile tourism development with the protection and conservation of the environment.
Keywords: 330